Intervenciones de enfermería en la prevención de adicciones. - Velastegui Motoche, Ronald Andres (2024)
In this research work, addictions, specifically drug addiction, were analysed as a public health problem worldwide. According to recent statistical data, this problem is one of the leading causes of morbidity and mortality in adolescence. In this context, the population group generates high levels of dependence to the point of perpetrating acts of vandalism for acquiring substances. In this sense, the repercussions presented denote the need to carry out essential interventions at the individual and environmental level in order to achieve a reduction in consumption demand. The development of preventive measures is essential, aimed at eliminating or modifying risk factors by promoting protective actions against drug use. The objective is to conduct a bibliographic review of nursing interventions for the prevention of addictions at the first level of care. The methodology was descriptive through the review of indexed scientific bases such as Scielo, Pubmed, Redalyc, Scopus, Elsevier, ProQuest, and articles related to drug addiction and health published from 2018 to 2024, determining that the most effective interventions at the first level of care are focused on the individual, the family, and the community and include actions to strengthen the family bond, problem solving, sentimental attachment, effective communication, active listening, social integration, leisure activities, and promotion of self-confidence, highlighting that these interventions must be worked from a multidisciplinary approach including social and community actors